1991
DOI: 10.1172/jci115084
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of integrin expression by nerve-derived connective tissue cells. Human Schwann cells, perineurial cells, and fibroblasts express markedly different patterns of beta 1 integrins during nerve development, neoplasia, and in vitro.

Abstract: Strikingly selective expression patterns of 61, a2, a3, and a5 integrin subunits were revealed in endoneurium, perineurium, and epineurium of fetal and adult human peripheral nerve by immunostaining with specific antibodies. The a2 subunit was expressed only on Schwann cells both in fetal and adult nerve, whereas the a3 epitopes were expressed exclusively in the adult tissue and were primarily present on perineurial cells. The a5 epitopes were expressed only on the innermost cell layer of perineurium of fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…As shown in Fig. 1, Schwann cells express a1b1, a3b1, a6b1, and a7b1 integrins and dystroglycan, consistent with previous results (Edgar, 1991;Hsiao et al, 1991;Milner et al, 1997;Previtali et al, 2003a;Stewart et al, 1997). We did not detect a2b1 integrin in Schwann cells (Fig.…”
Section: Schwann Cells Express Several Laminin-binding Receptorssupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Fig. 1, Schwann cells express a1b1, a3b1, a6b1, and a7b1 integrins and dystroglycan, consistent with previous results (Edgar, 1991;Hsiao et al, 1991;Milner et al, 1997;Previtali et al, 2003a;Stewart et al, 1997). We did not detect a2b1 integrin in Schwann cells (Fig.…”
Section: Schwann Cells Express Several Laminin-binding Receptorssupporting
confidence: 92%
“…Expression of a7 integrin is detected in neonatal and adult peripheral nerve, but not in embryonic nerves (Previtali et al, 2003a,b). In contrast, both a6 and a2 integrins are detected in embryonic nerves (Hsiao et al, 1991;Previtali et al, 2003b). We found that Schwann cell a6b1 integrin does not bind to laminin-2.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For comparison, the effects of these inhibitors on adhesion to collagen type IV were also determined. The best-characterized cellular receptors for collagen molecules are ␣1␤1-and ␣2␤1-integrins (Dickeson et al, 1999;Knight et al, 2000;Nykvist et al, 2000), which are expressed by Schwann cells (Hsiao et al, 1991;Milner et al, 1997). The function-blocking monoclonal anti-␣1-integrin antibody inhibited Schwann cell adhesion to collagen type IV by ϳ50% (Fig.…”
Section: Schwann Cell Adhesion and Spreadingmentioning
confidence: 99%
“…Two lines of recent research have provided the tools to investigate the events of glucose metabolism of the neural connective tissue at the cellular level in a detailed manner: first, the characterization of sodium-independent GLUTs, a family of membrane-associated proteins that are responsible for facilitated diffusion of D-glucose into mammalian cells (4,5); and secondly, the development of a cell-culture method that allows identification of perineurial cells, Schwann cells, and neural fibroblasts, and assessment of their gene expression profiles in mixed cultures (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%